2003
DOI: 10.1557/jmr.2003.0123
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of Cu60Ti20Zr20 metallic glass with and without pressure

Abstract: Structural stability of a Cu 60 Ti 20 Zr 20 metallic glass under pressure up to 4.5 GPa was investigated by x-ray diffraction. The sample exhibited a supercooled liquid region of 33 K and a ratio of the glass-transition temperature to the liquidus temperature of 0.63. The glass crystallized in two-step transformation processes in the pressure range of 0-4.5 GPa; the first was a primary reaction to form a Cu 51 Zr 14 -type structure crystalline phase with a spacing group P6/m (175) and lattice parameters a ‫ס‬ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
33
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 22 publications
(17 reference statements)
5
33
0
Order By: Relevance
“…The DSC curve for the as-cast rod is in good agreement with data reported in the literature. [5][6][7][8][9][10][11][12] With increasing annealing time, the enthalpy of the first exothermic peak monotonically decreases from 25 J/g for the as-cast rod to about 5 J/g for the sample annealed for 7.8 ks, while the second exothermic peak remains almost unchanged within experimental uncertainty. With further increasing annealing time, the second exothermic peak starts to decrease and its position shifts to low temperatures.…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…The DSC curve for the as-cast rod is in good agreement with data reported in the literature. [5][6][7][8][9][10][11][12] With increasing annealing time, the enthalpy of the first exothermic peak monotonically decreases from 25 J/g for the as-cast rod to about 5 J/g for the sample annealed for 7.8 ks, while the second exothermic peak remains almost unchanged within experimental uncertainty. With further increasing annealing time, the second exothermic peak starts to decrease and its position shifts to low temperatures.…”
mentioning
confidence: 89%
“…[2][3][4] Very recently, the report of ternary Cu 60 Ti 10 Zr 30 and Cu 60 Ti 15 Hf 25 systems, 5,6 exhibiting excellent mechanical properties, has triggered considerable research activity in this area, especially in the microstructure of the ternary systems. [5][6][7][8][9][10][11][12] Inoue et al, 5,6 reported that bulk glassy alloys with a rod diameter of 4 mm can be formed in the ternary Cu 60 Ti 10 Zr 30 and Cu 60 Ti 15 Hf 25 systems. However, only the x-ray diffraction ͑XRD͒ technique was applied to characterize the samples.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recrystallization of amorphous phases under pressure has been observed in amorphous − quartz [62], which transforms into stishovite at about 60 GPa, and for the high-density amorphous phase of ice [63], which recovers the ice VII or ice VIII structure at high pressure. Recrystallization under pressure or stress is also observed in a number of glasses [64]. On the other hand, superhard properties, i.e.…”
Section: Epj Web Of Conferencesmentioning
confidence: 95%
“…12,13 DSC measurements of the as-rolled specimens with different indicate that the areas of the both exothermic peaks are almost unchanged compared to the as-cast specimen ͑not shown here͒. So, the possibility of crystallization in the asrolled specimens can be excluded.…”
mentioning
confidence: 94%